(x-3)(3x+5)=0

Simple and best practice solution for (x-3)(3x+5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-3)(3x+5)=0 equation:


Simplifying
(x + -3)(3x + 5) = 0

Reorder the terms:
(-3 + x)(3x + 5) = 0

Reorder the terms:
(-3 + x)(5 + 3x) = 0

Multiply (-3 + x) * (5 + 3x)
(-3(5 + 3x) + x(5 + 3x)) = 0
((5 * -3 + 3x * -3) + x(5 + 3x)) = 0
((-15 + -9x) + x(5 + 3x)) = 0
(-15 + -9x + (5 * x + 3x * x)) = 0
(-15 + -9x + (5x + 3x2)) = 0

Combine like terms: -9x + 5x = -4x
(-15 + -4x + 3x2) = 0

Solving
-15 + -4x + 3x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-5 + -3x)(3 + -1x) = 0

Subproblem 1

Set the factor '(-5 + -3x)' equal to zero and attempt to solve: Simplifying -5 + -3x = 0 Solving -5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = 0 + 5 -3x = 0 + 5 Combine like terms: 0 + 5 = 5 -3x = 5 Divide each side by '-3'. x = -1.666666667 Simplifying x = -1.666666667

Subproblem 2

Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3

Solution

x = {-1.666666667, 3}

See similar equations:

| 3/4-1/2b=3b | | 7x+5=13x+5 | | -8z-7=3z-7+5z | | x^2+3x-6=7x+6 | | -18-6=(1+3x) | | 23x-29y=7 | | 5x^2(6x+2)= | | 4x^2+4xy^2+y^4= | | 200=(50-2x)(20-2x) | | 6xz-5x= | | 2(a+12)=4 | | 2(x+4)=4+2x | | 18/12=m/42 | | 6d+5d=-11 | | 3x+2-4(8-7)=90 | | 10+x-1/3x+0 | | 35=-5+2g-7g | | b+27.51=36 | | -8n-3=-11 | | b/2-4=-8 | | -8n-3=-10 | | -8n-3=-83 | | x/2-5=-7 | | 2y^2-7y-15= | | 6x+45=9(x+5)-3x | | r/5+2=0 | | x/0.25 | | -1/5p+3/4p=11 | | -y=2(-2)-8 | | w+31=50 | | 2x+y+1=0 | | 6.7+p=10.4 |

Equations solver categories